2013
DOI: 10.1371/journal.pone.0081477
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Antimicrobials to Induce Thrombocytopenia in Critically Ill Patients: Data from a Randomized Controlled Trial

Abstract: BackgroundAntimicrobial-induced thrombocytopenia is frequently described in the literature among critically ill patients. Several antimicrobials have been implicated, although experimental evidence to demonstrate causality is limited. We report, using a randomized trial, the potential of antimicrobials to induce thrombocytopenia.MethodsRandomized trial allocated patients to antimicrobial treatment according to standard- of-care (SOC group) or drug-escalation in case of procalcitonin increases (high-exposure gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
12
1
1
Order By: Relevance
“…Although antimicrobial‐induced thrombocytopenia has been extensively described in the literature, to the best of our knowledge, this is the first confirmed case of meropenem‐induced immune thrombocytopenia. Upon additional literature review, however, we found several case reports and series documenting instances in which meropenem or other carbapenems caused severe thrombocytopenia . However, in these cases, there was no further testing of the patients' blood for drug‐induced antibodies, so we cannot definitively know whether these cases were actually DITP.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Although antimicrobial‐induced thrombocytopenia has been extensively described in the literature, to the best of our knowledge, this is the first confirmed case of meropenem‐induced immune thrombocytopenia. Upon additional literature review, however, we found several case reports and series documenting instances in which meropenem or other carbapenems caused severe thrombocytopenia . However, in these cases, there was no further testing of the patients' blood for drug‐induced antibodies, so we cannot definitively know whether these cases were actually DITP.…”
Section: Discussionmentioning
confidence: 73%
“…After discontinuing the offending drug, bleeding most often stops within 2 days, and the PLT count returns to normal in 4 to 7 days. 11 Although antimicrobial-induced thrombocytopenia has been extensively described in the literature, 12,13 to the best of our knowledge, this is the first confirmed case of meropenem-induced immune thrombocytopenia. Upon additional literature review, however, we found several case reports and series documenting instances in which meropenem or other carbapenems caused severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The explanation for this result may be that there is a “neutralising” effect, involving harm from antibiotics counteracting any benefits from better timing of their administration. Notably, several harmful effects were reported from the “high-intensive” antibiotic strategy in the PCT-guided arm of the trial: an increase in the risk of renal failure that was attributed to piperacillin [ 100 ], a ciprofloxacin-associated increase in the risk of invasive fungal infection [ 101 ] and haematological side effects [ 102 ]. Most of the patients who had been classified as high risk (i.e., those with severe sepsis or septic shock) were already being given broad-spectrum antibiotics.…”
Section: Treatment Response Biomarkersmentioning
confidence: 99%
“…Do fl uorochinolonów rekomendowanych w szpitalnym receptariuszu należą: ciprofl oksacyna, lewofl oksacyna, moksyfl oksacyna oraz norfl oksacyna. Wskazania do stosowania w poszczególnych sytuacjach klinicznych przedstawia tabela 1: Tabela [3,7,8,9,10,11]. Zastosowanie tej grupy antybiotyków u dzieci zostało ograniczone, gdyż w badaniach wykazano, że u młodych zwierząt uszkadzają one chrząstkę wzrostową, powodując -na ogół nieodwracalną -artropatię.…”
Section: Wskazania Do Stosowaniaunclassified